Does Consumers' Awareness Impact Their Purchase Likelihood of Neonic-Free Plants? - Hayk Khachatryan; Alicia L. Rihn (EDIS, 2017)
Neonicotinoid (neonic) pesticides have been facing intense scrutiny because of their potential role in pollinator insect population declines. Research has shown that insecticide use in general has resulted in $284 million per year in damages to honeybee and pollinator services in the United States. This is especially worrying because food supply would fail to meet increasing global food demand without pollinator insects.